Consumer acceptance of quality protein maize (QPM) in East Africa. (8th May 2014) - De Groote, Hugo; Gunaratna, Nilupa S; Okuro, James O; Wondimu, Asrat; Chege, Christine K; Tomlins, Keith
Abstract BACKGROUND Undernutrition in sub‐Saharan Africa remains problematic, and quality protein maize (QPM) can benefit populations whose diets are heavily based on maize and who are consequently at risk for inadequate intakes of quality protein. However, changes in the chemical composition of QPM may affect its sensory characteristics and, hence, acceptance. Acceptance tests were therefore conducted to evaluate QPM varieties in three East African countries using central location tests with one or two varieties in each country, using the most popular preparations: ugali (Tanzania), githeri (Kenya) and injera (Ethiopia). In total, 281 urban and rural consumers of both sexes and varying levels of education evaluated the products on standard sensory criteria: appearance, aroma, texture, taste and overall, using a Likert scale. RESULTS The results show that African consumers can differentiate QPM products from their conventional counterparts, indicating that the QPM trait results in distinguishable sensory changes. Analysis by ordinal mixed regression models showed that consumers found QPM acceptable and even preferable to conventional maize. CONCLUSION The sensory characteristics of QPM are therefore no impediment to its adoption; on the contrary, when coupled with good agronomic performance, they may help its utilization, leading to a positive impact in nutritionally vulnerable populations. © 2014 Society of Chemical Industry